Associations of sleep pattern, sleep duration, bedtime, rising time and cardiovascular disease: Data from NHANES (2017–2020) - Xiao Zhang; Dongling Wang; Jiangang Liu (PLoS ONE, 2025)
Background Sleep has a significant impact on the incidence of cardiovascular diseases (CVD), but there is no comprehensive research on this topic. Aims Assess the association between sleep factors and the risk of cardiovascular diseases in terms of comprehensive sleep behavior. Methods This study included 8,075 subjects from NHANES 2017–2020, excluding those with missing sleep/CVD data. Poor sleep factors: abnormal sleep duration (<7h or>8h), trouble sleeping, snoring, snort or stop breathing, sleepy during day. Each factor was scored (0–12 total), classifying sleep patterns as healthy (0–4), intermediate (5–8) or poor (9–12). Multivariable logistic regression analyzed the association between unhealthy sleep and CVD. Weighted data were used for restricted cubic spline (RCS) plots to assess the nonlinear relationship between sleep durations, bedtime, rising time and CVD. Results Adjusted models showed significant associations between poor sleep and heart failure, myocardial infarction, stroke and hypertension (p < 0.05). Daytime sleepiness also increased stroke and hypertension risks (p < 0.05). RCS plots revealed nonlinear relationships: 7–9 hours sleep/day minimized heart failure, myocardial infarction and hypertension risks; 6–8 hours/day minimized stroke risk. Bedtime showed J-shaped and U-shaped associations with myocardial infarction and hypertension. Conclusion This nationally representative survey revealed that poor sleep patterns, particularly sleep disorders, daytime sleepiness and reported breathing obstructions were significantly associated with an increased prevalence of cardiovascular diseases. Additionally, there was a nonlinear correlation between sleep duration, bedtime, rising time and the risk of developing cardiovascular diseases.